Implementation of the Teaching at the Right Level (TaRL) Approach through Differentiated Learning on Biographical Text Material at SMA Negeri 1 Mataram - Herdikayanti, Yenita; Rizky Romdani, Muhammad; Diniyati, Diniyati; Arista, Widya; Maemunah, Maemunah; Sunarti, Sunarti; Sugino, Sugino (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The aim of this research is to find out how to implement the Teaching at The Right Level (TaRL) approach through differentiated learning on Biographical Text material at SMA Negeri 1 Mataram which is integrated with the Merdeka Belajar Curriculum. There are several objectives for implementing differentiated learning, including: 1) meeting the individual needs of students; 2) increase student achievement; 3) increase students' motivation and interest in learning; 4) develop social and collaborative skills; 5) increase students' self-esteem; and 6) increasing student involvement. The application of differentiated learning places the teacher as a facilitator who helps students meet their needs. In differentiated learning, the teacher provides an understanding of the material by paying attention to the level of readiness, interests and learning styles of students. Apart from that, teachers can also make modifications to lesson content, learning processes, products or results of the lessons taught, and the learning environment.